Application of the Concept of Diffusion of Innovations in Tourism Support Business Sustainability: Study at Loempia Lanny Semarang - Agung Sulistyo; Dena Danella; Susiyanto Susiyanto (Majalah Bisnis & IPTEK, 2023)
The instrument of diffusion innovation concept has been widely used in creating a sustainable business. Growing business and competitive competition are forcing business actors to think hard. The idea of innovation is made as one of the efforts that can be made. Existing instruments, such as innovation, time, communication channels, and social system, can guide business actors in implementing business management. This study aims to analyze the application of innovation diffusion at Loempia Lanny Semarang. This study uses a qualitative study design combined with a case study approach. They are collecting data in this study using interview techniques combined with the concept of diffusion innovation. Sources of information were obtained through the narrative of predetermined informants: business managers, employees, and consumers who are enjoying Loempia Lanny products. Data validation and processing used triangulation techniques and the Miles Huberman method through interview transcription, reduction, coding, categorization, and concluding. Based on the research results, it is known that Loempia Lanny's business follows the concept of innovation diffusion. The business manager has implemented all the instruments used. The research confirms that the idea of innovation has been implemented. However, business actors need to reinvent innovation to manage a sustainable business so that it is maintained.